2018
DOI: 10.3892/ol.2018.9226
|View full text |Cite
|
Sign up to set email alerts
|

Novel strategy of sirolimus plus thymalfasin and huaier granule on tumor recurrence of hepatocellular carcinoma beyond the UCSF criteria following liver transplantation: A single center experience

Abstract: Although liver transplantation (LT) lengthens the survival time of patients with hepatocellular carcinoma (HCC), LT patients exhibit a high recurrence rate; particularly those that had advanced HCC associated with the tumor biological characteristics and long-term application of immunosuppressants. A consensus on optimal prophylaxis and treatment for recurrent HCC following LT does not currently exist. The present study retrospectively analyzed data from 36 non-University of California at San Francisco criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
(76 reference statements)
0
15
0
Order By: Relevance
“…Additionally, histone deacetylase inhibitor trichostatin A has seen anti-HCC efficacy by activating cell death signalling cascades [ 61 ]. More importantly, a single-centre study demonstrated the favourable effect sirolimus has on HCC patients, whose survival time were longer than in the control group [ 62 ]. Therefore, such evidence indicates that repurposing FDA-approved small molecule drugs is a promising direction for HCC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, histone deacetylase inhibitor trichostatin A has seen anti-HCC efficacy by activating cell death signalling cascades [ 61 ]. More importantly, a single-centre study demonstrated the favourable effect sirolimus has on HCC patients, whose survival time were longer than in the control group [ 62 ]. Therefore, such evidence indicates that repurposing FDA-approved small molecule drugs is a promising direction for HCC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Coincidentally, Xu et al [ 49 ] found that the recurrence-free survival rate of HCC transplant patients meeting the Milan criteria was not significantly different between the RAPA group and the control group, but under the intervention of RAPA, the overall survival time of the patients after recurrence was significantly longer than that of the control group. As one of the earliest transplant centers to use RAPA conversion therapy in China[ 13 , 50 ], we suggested that early conversion of RAPA after transplantation can improve the survival benefits of patients. The results of our previous study showed that RAPA-based therapy improved post-LT survival rates and decreased recurrence rates compared with the control group after LT.…”
Section: Trends Of Rapa In Survival Benefits Of Transplant For Hccmentioning
confidence: 99%
“…RAPA is presently employed as an immunosuppressant in recipients with abnormal renal function, intolerable adverse reactions of CNIs, and the high risk of post-LT recurrence, and it can provide sufficient immunosuppression while reducing the risk of recurrence, renal impairment, and infection[ 12 ]. Since 2011, our team has taken the lead in the application of RAPA conversion therapy in HCC transplant patients in China and recommended RAPA as the main immunosuppressive treatment strategy[ 13 ]. In recent years, the proportion of immunosuppressive regimens based on RAPA in HCC transplant patients has kept on increasing, but in the clinical treatment of such patients, there are still many controversies about the impact of RAPA on the survival benefits.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used in Chinese Medicine for nearly 1600 years [14][15][16][17][18]. Huaier granule, the aqueous product of Huaier extract, is an approved traditional Chinese biomedical preparation (TCBP) by Chinese State Food and Drug Administration (SFDA) to be used alone or combined with other drugs in treatment of various malignant tumors including breast cancer, liver cancer, and gastric cancer [17][18][19][20][21]. Recent studies show that the active ingredient in Huaier extract is a proteoglycan, composed of 41.5% polysaccharides, 12.93% amino acids and 8.72% water [18,22].…”
Section: Introductionmentioning
confidence: 99%